Javanese Values Integration in Business Management During The Digital Era: A Case Study of Entrepreneurs in Malang - Adhy Wicaksono; Heri Pratikto; Agung Winarno (Universitas Negeri Malang, 2020)
This study aims at describing the characteristics of Javanese entrepreneurs in facing the digital age, the views and attitudes of Javanese entrepreneurs in entrepreneurship in the digital age, to describe the processes experienced by Javanese ethnic entrepreneurs in facing the digital age. The approach used in this study used a qualitative research approach using the type of case study research, data collection procedures used were observation, and in-depth interviews. In order to be able to obtain the validity of the data, data source triangulation was conducted by comparing the results of the interview findings of business owners as key informants with parents, employees, and customers. The subjects of this study were the owners of two stores in Malang, specifically the owner of Distro Overtoun and Art Printing stores. In this study, it was found that the characteristics of entrepreneurs and the values of Javanese culture can go hand in hand. The views and attitudes taken by the two entrepreneurs are also more open in facing the digital age. Meanwhile, the processes experienced in facing the digital age run efficiently.